Upper Cretaceous (Maastrichtian) ammonites from the Nostoceras alternatum zone in southwestern Arkansas - Cobban, W; Kennedy, W (1991)
Calcareous concretions in the Nacatoch Sand in Hempstead County, Arkansas, yield abundant fossils of the lower Maastrichtian Nostoceras alternatum zone, previously recognized in Mississippi, Alabama, and Georgia. The fossils include Inoceramus regularis d'Orbigny, 1842, Pseudophyllites indra (Forbes, 1846), Brahmaites sp., Sphenodiscus sp., Nostoceras (Nostoceras) alternatum (Tuomey, 1854), Solenoceras nitidum Cobban, 1974, Baculites claviformis Stephenson, 1941, and Jeletzkytes sp. A and sp. B. The N. alternatum zone may correlate with the Baculites clinolobatus zone in the Western Interior. -Authors